Multimedia educational game approach for psychological conditional - Nasrudin, N; Agustina, Ika; Akrim, A; Saleh Ahmar, Ansari; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
This study aimed to develop Multimedia-Based Educational game for junior high school students grade IX and investigate its effectiveness on student’s learning psychological condition in facing computer-based National Exam it is called UNBK in indonesia. Population of this research is junior high school students grade IX Muhammadiyah 1 Medan. Sample using in this research were two class that amount 64 students chosen randomly. The result product verified by some experts showed that the multimedia–based educational game is appropriate to use as a learning medium for students in preparing Computer-based national exam. Then, the calculation of Independent samples t-test showed that sig. (2-tailed) was 0.000. It’s lower than 0.05, it meant that there was significant effect by using multimedia-based national exam on student’s learning psychological condition in facing computer-based national exam. Student had high motivation, stronger interest, and positive attitude in facing UNBK. Students claimed they had greater motivation to challenge UNBK, motivation to continue studies to high school. In addition to motivation, they also expressed greater interest in the particular tested sub-jects, an interest in choosing majors. Student attitude also more positive with more intense when discuss, review the mate-rial that has been presented, feel challenged and focus in learning.